Nigeria : Insurance Core Principles - International Monetary Fund; World Bank (World Bank, Washington, DC, 2013)
This assessment provides an update on the significant regulatory and supervisory development in the Nigerian insurance sector since 2001. Nigeria undertook an initial Financial Sector Assessment Program (FSAP) in December 2001, which included a review of the structure of Nigeria's insurance market and the supervisory framework and approach. Nigeria has also undertaken reviews of its observance of international accounting and auditing standards (2004 and 2011), and corporate governance (2008). The Nigerian authorities have taken steps to address a number of weaknesses identified in the 2001 FSAP. The assessment was benchmarked against the Insurance Core Principles (ICPs) issued by the International Association of Insurance Supervisors (IAIS) in October 2011. As the compulsory insurance is enforced, the cost of intermediation of compulsory insurance and the purchase of retirement annuities need to be addressed to improve efficiency of the market. This note is structured as follows: chapter one gives key findings and recommendations; and chapter two gives detailed assessment.